Synthesis, Experimental and Theoretical Study of Azidochromones - Ena G. Narváez-Ordoñez; Kevin A. Pabón-Carcelén; Daniel A. Zurita-Saltos; Pablo M. Bonilla-Valladares; Trosky G. Yánez-Darquea; Luis A. Ramos-Guerrero; Sonia E. Ulic; Jorge L. Jios; Gustavo A. Echeverría; Oscar E. Piro; Peter Langer; Christian D. Alcívar-León; et al. (Molecules, 2022)
A series of 2-(haloalkyl)-3-azidomethyl and 6-azido chromones has been synthetized, characterized and studied by theoretical (DFT calculations) and spectroscopic methods (UV-Vis, NMR). The crystal structure of 3-azidomethyl-2-difluoromethyl chromone, determined by X-ray diffraction methods, shows a planar framework due to extended π-bond delocalization. Its molecular packing is stabilized by F···H, N···H and O···H hydrogen bonds, π···π stacking and C–O···π intermolecular interactions. Moreover, AIM, NCI and Hirshfeld analysis evidenced that azido moiety has a significant role in the stabilization of crystal packing through weak intermolecular interactions, where analysis of electronic density suggested closed-shell (CS) interatomic interactions.